Enzymatic Kinetic Resolution of Tertiary Benzyl Bicyclic Alcohols: Studies of the Reaction Conditions for a More Efficient Protocol - de Almeida, Laiza A. [UNESP]; Neto, Laerte Ganéo [UNESP]; Milagre, Cintia D.F. [UNESP]; Milagre, Humberto M.S. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2024)
The reactivity and steric hindrance of optically active tertiary alcohols limit the development of more direct enantioselective methodologies for their synthesis, such as kinetic resolution (KR). In this work, we optimized the reaction conditions of an enzymatic KR of two tertiary benzyl bicyclic alcohols using readily available reagents and biocatalyst. Studies were conducted with 1-methyl-1,2,3,4-tetrahydronaphthalen-1-ol and 1-methyl-2,3-dihydro-1H-inden-1-ol as substrates and commercial lipase A from Candida antarctica (CAL-A) as biocatalyst for the enantioselective transesterification of these racemic tertiary alcohols. After varying the reaction parameters, such as acyl donor, solvent, and enzyme/substrate ratio, the (R)-esters were obtained with high conversions (44-45%) and excellent enantiomeric excess (96-99%) in only 4-5 h, to our knowledge being the best result for KR of the evaluated tertiary alcohols in terms of reaction rate, conversion, and enantioselectivity reported so far.
Keywords: enantioselective transesterification; kinetic resolution; lipase; tertiary alcohol